Thermal-flow analysis of the operation of a geothermal CHP power plant based on the ORC cycle cooperating with a Field-type exchanger - Wiśniewski, Sławomir; Kujawa, Tomasz (Instal, 2024)
powered by geothermal energy obtained via a deep geothermal Field exchanger. In the analyzed geothermal CHP plant system with a low-boiling ORC circuit, heat for central heating purposes can be obtained from steam leaving the ORC system turbine or directly from the Field exchanger. As the analysis shows, such a solution allows for significant regulation of the heat flux for heating purposes, by changing both the mass flow rate of the heating medium and its temperature. The proposed solution also allows the system to function as a heating plant (only for heating purposes), and in the absence of heat demand for heating purposes, as a power plant (only electricity). This approach increases the flexibility of the proposed solution and allows for better use of geothermal energy resources obtained using a Field exchanger. In the analysis of the geothermal power plant system, the variability of the operating parameters of the ORC system itself for three different working fluids (R1234ze, R1234yf and R227ea) and the variable characteristics of the Field heat exchanger (change of the water flow) were taken into account.
Keywords: geothermal energy; geothermal combined heat and power plant; ORC cycle; low-boiling medium; Field-type exchanger